Penatalaksanaan Fisioterapi Pada Kasus Osteoarthritis Lutut Dextra Di RSUD Sukoharjo - Agustin, Istimufidhah Dian Rela; , Umi Budi Rahayu SST FT, S.Pd,.M.Kes (2015)
Background: Osteoarthritis is a disorder of the joints moving. This disease is chronic, slowly progressive running, not inflamed and marked by the deterioration and erosion of cartilage and the formation of new bone at the joint surface. Physiotherapy modalities used are TENS to reduce pain. And therapy is done with the method of free active exercise, active resisted exercise, and hoald relax, beneficial to reduce pain, increase range of motion, increase muscle around the joints. Objective: To mengetahuai TENS effect on reducing pain in patients with osteoarthritis of the knee, to know the effect of exercise therapy to increase range of motion (LGS), know the effect of exercise therapy to increase muscle strength around the knee joint, know the effect of exercise therapy to increase the ability of functional activity based scale Jette. Results: After treatment as 6kali in getting research results pain, tenderness silent T1: 2 to T6: 1, painful motion T1: 5 to T6: 4, T1 flexor muscle strength: 4- become T6: 4+, extensor muscle strength T1 : 4- become T6: 4+, increase range of motion active movement T1: S 0-0-125 be T6: S-0-0-135, passive range of motion movements T1: S 0-0-130 be T6: S 0-0-135, anthropometric increase at the start of the umbilicus - lateral malleolus: 60 cm to T1: 60 cm to T6: 60 cm, SIAS - the medial malleolus: 60 cm to T1: 60 cm to T6: 60cm, increase the functional capability of the position stands sitting, pain T1: 1 to T6 1, difficulty T1: 2 to T6: 2, dependence T1: 1 to T6: 1, walk 15 meters, pain T1: 2 to T6: 1, difficulty T1: 2 to T6: 1, dependence T1: 1 to T6: 1, go up the stairs three traps, pain T1: 2 to T6: 2, difficulty T1: 2 to T6: 2, dependence T1: 1 to T6: 1. Conclusions:Transutaneus Electrical Nerve Stimulation (TENS) can reduce pain, exercise therapy is free of active exercise, active resisted exercise, and hoald relax, beneficial to reduce pain, increase range of motion, meiningkatkan muscles around the joint.